1995
DOI: 10.1063/1.114753
|View full text |Cite
|
Sign up to set email alerts
|

Be diffusion mechanisms in InGaAs during post-growth annealing

Abstract: Be diffusion during post-growth annealing has been studied in InGaAs epitaxial layers, grown between two undoped InGaAs layers. To explain the observed concentration profiles and related diffusion mechanisms, a general substitutional–interstitial model is proposed. On the one hand, a simultaneous diffusion by dissociative and kick-out models is suggested and, on the other hand, the Fermi-level effect is used to explain the functional dependence change of the effective diffusion coefficient of beryllium species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…For example, in Ref. [ 3 ], the authors "suggest the case of neutral beryllium interstitials" (emphasis is ours). This is in spite of a well-known propensity of interstitial alkali earth atoms to donate both their valence electrons to Page 5 of 27 the conduction band of the semiconductor host [ 10,11,13,35 ]; the donation of two electrons to the conduction band was also explicitly computed for interstitial Be in InGaAs in Ref.…”
Section: Page 4 Of 27mentioning
confidence: 99%
“…For example, in Ref. [ 3 ], the authors "suggest the case of neutral beryllium interstitials" (emphasis is ours). This is in spite of a well-known propensity of interstitial alkali earth atoms to donate both their valence electrons to Page 5 of 27 the conduction band of the semiconductor host [ 10,11,13,35 ]; the donation of two electrons to the conduction band was also explicitly computed for interstitial Be in InGaAs in Ref.…”
Section: Page 4 Of 27mentioning
confidence: 99%
“…3,4 A controlled selective area doping of InGaAs layers is required to fully exploit this material potential, and ion beam implantation has emerged as a versatile doping technique to realize the complex doping profiles required for device fabrication. Monolithic planar integration of a high-performance photodiode-junction-field-effect transistor combination has been achieved by using local Si-and Be-ion beam implantations to fabricate a junction field effect transistor on an optimized InGaAs/InP photodiode layer.…”
Section: Introductionmentioning
confidence: 99%
“…Be (and Zinc) diffusion were found based on Substitutional-Interstitial Diffusion mechanism (SID), and more precisely, on dissociative [1][2][3][4] or kick-out [5,6] models. Some authors even found that the second model has an advantage over the first [6,71. In contrast, investigations on p-type dopant diffusion in InP based epitaxial compounds, in particular Be in InGaAs, are still limited [8,9,10].…”
Section: Introductionmentioning
confidence: 88%